Coexistence of He and H in ceramic insulators for the DCLL Breeding Blanket: Evaluation of potential synergistic effects by TEM and nanoindentation - M. Roldán; J.M. García; M. González; V. Bonache; J. Rams (Nuclear Materials and Energy, 2025)
The development of ceramic insulators for fusion applications requires a detailed understanding of their microstructural and mechanical responses under radiation conditions representative of transmutation gas generation. In this work, polycrystalline alumina (Al2O3) and silicon-infiltrated silicon carbide (SiC-Si) ceramics were subjected to sequential helium (He) and hydrogen (H) ion implantation at MeV energies to evaluate potential synergistic effects on damage accumulation. Ion stopping profiles were designed to produce overlapping damage regions, and the resulting microstructures were examined by focused ion beam lamellae and transmission electron microscopy (FIB+TEM), while mechanical properties were assessed by nanoindentation. In Al2O3, irradiation induced a high density of nanocavities of nanocavities and dislocation loops, with cavity alignment possibly influenced by hydrogen-induced local strain fields. Conversely, SiC-Si showed a minimal presence of visible defects, suggesting effective recombination mechanisms at SiC/Si interfaces. Hardness increased modestly in both materials—by ∼ 8% in Al2O3 and ∼ 20% in SiC-Si—consistent with the presence of dispersed radiation defects. No evidence of enhanced damage due to He–H synergy was observed, as the microstructural and mechanical changes were consistent with the additive effects of each ion species. These results support the suitability of Al2O3 and, particularly, SiC-Si for use as insulating components in the Dual Coolant Lithium Lead (DCLL) breeding blanket of the future DEMO fusion reactor.